ANALISIS PENGARUH SUHU MINYAK KELAPA SAWIT (CPO) TERHADAP NILAI TAHANAN TERMAL MEMPERGUNAKAN PEMODELAN KURVA I(V) ISOTERMAL SENSOR PTC - Dellia Yulita; Lazuardi Umar (Program Studi Fisika Universitas Negeri Jakarta, 2017)
PTC level sensor for overfill protection works based on the thermal resistance (Rw). The sensor cannot identify high-temperature fluid in the container and determine the pump switching status Ã¢â‚¬Å“ONÃ¢â‚¬Â and Ã¢â‚¬Å“OFFÃ¢â‚¬Â. This is due to the influence of the medium temperature on the Rw. Analysis is performed by observing the Rw value of crude palm oil (CPO) as a result of the storage temperature. The Rw value was obtained from the modeling of I (U) sensor curve of EPCOS B59050D1100 with temperature variations ranging from 20Ã‚Â°C to 80Ã‚Â°C. The modeled area is then determined using the isothermal curve and is resulted Rw value of 110.2K/W. The ambient temperature influence on Rw can be modeled after polynomial equation. Compare to the previous air measurement, the thermal resistance in CPO has 62.6% vary than in the air. This value can be used to determine the position of the level sensor switch safely. Keywords: level sensors, PTC, thermal resistance, CPO, isothermal